Minnie D. Morgan - Farrell Hoy Jenab (Symphony in the Flint Hills, 2016)
Wilhelmina (Minnie) D. Morgan was the first female mayor of Cottonwood Falls, Kansas.
Keywords: history; Chase County; mayorship; Kansas politics; activism; sheer perseverance; U.S. Constitution; BREATH; Shin-hee Chin; FAITH; Allan Chow; PRAIRIE; REMEMBERED 1; Kelly Yarbrough